Adsorption of pyridine and phenol from organic-mineral mixture by the acide-treated activated carbons - O Vladimirovna Belyaeva; N Sergeevna Golubeva; T Andreevna Krasnova (RUDN Journal of Engineering Research, 2011)
Adsorption of phenol and pyridine from organic-mineral wastewater with the help of acide-treated activated carbons has been investigated. It was shown that the modifying of adsorbents increases adsorption of organic components. Adsorption capacity change depends on the activated carbon nature.